FIRST-PRINCIPLES INSIGHTS ON THE BONDING MECHANISM OF DIRECT-STACKED BIPHENYLENE NETWORK - Art Anthony Z. Munio; Alvanh Alem G. Pido; Kenneth Ian M. Balili (International Engineering Journal For Research & Development, 2022)
Recently, a new class of carbon-based nanomaterial (biphenylene network) was synthesized and gained much attention in the scientific community. Using first-principles method, we explored the bonding mechanism of direct-stacked biphenylene networks. Our calculations suggest that the nature of the interaction between the layers of the network is due to van der Waals interaction. This is due to the weak binding energy between the biphenylene networks and the deformed Electron Localization Function in the interface. We anticipate that this work will serve as a reference for further scientific investigation on the biphenylene network.